2022
DOI: 10.15562/bmj.v10i3.2925
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological malignancy with obstructive uropathy patient profile in Cipto Mangunkusumo Hospital: Our 2-year experience

Abstract: Introduction: Gynecological malignancies are one of the most common causes of death from cancer in women. Hydronephrosis or obstructive uropathy is the most common finding in patients with gynecological malignancy. This study aimed to describe the profile of obstructive uropathy patients causes of gynecology malignancies treated in our center from 2019 to 2021. Method: From January 2019 to January 2021, obstructive uropathy patients with gynecological malignancies who underwent DJ stent or nephrostomy insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Our research showed that DJ stent placement was successful in 43 (48.9%) out of 88 patients, while unsuccessful stent insertion resulted in the need for nephrostomy. Our results differ significantly from a similar study conducted by Affan et al, in which 69.2% of cervical cancer patients required nephrostomy [ 3 ]. Obstructive uropathy in cervical cancer can lead to the development of hydronephrosis and kidney failure, both of which have a poor prognosis.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our research showed that DJ stent placement was successful in 43 (48.9%) out of 88 patients, while unsuccessful stent insertion resulted in the need for nephrostomy. Our results differ significantly from a similar study conducted by Affan et al, in which 69.2% of cervical cancer patients required nephrostomy [ 3 ]. Obstructive uropathy in cervical cancer can lead to the development of hydronephrosis and kidney failure, both of which have a poor prognosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Gynecological cancers such as ovarian, uterine, and cervical cancer are frequent causes of obstructive uropathy in women. Concurrent radiation and cisplatin-based chemotherapy are recommended as the first line of treatment for locally advanced cervical cancer, as they can lower the risk of death and recurrence [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations